2021
DOI: 10.1136/neurintsurg-2021-017361
|View full text |Cite
|
Sign up to set email alerts
|

Major complications of dural venous sinus stenting for idiopathic intracranial hypertension: case series and management considerations

Abstract: BackgroundVenous sinus stenting (VSS) is a safe, effective, and increasingly popular treatment option for selected patients with idiopathic intracranial hypertension (IIH). Serious complications associated with VSS are rarely reported.MethodsSerious complications after VSS were identified retrospectively from multicenter databases. The cases are presented and management strategies are discussed.ResultsSix major acute and chronic complications after VSS were selected from a total of 811 VSS procedures and 1466 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Although this may be only natural as new promising techniques are developed, this discrepancy may imply that the pervasive opinion on VSS in the neurointerventional community is that it is a ‘simple’ and safe procedure. However, there is a known 1–2% major complication rate even in experienced hands,4 and in this survey, 11% of respondents reported a major complication during a VSS procedure, with two reported deaths. Having a life threatening complication from VSS was more commonly reported in higher volume operators, which may naturally be expected due to a higher denominator of cases, or could be secondary to other nuanced factors that this survey was unable to identify.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although this may be only natural as new promising techniques are developed, this discrepancy may imply that the pervasive opinion on VSS in the neurointerventional community is that it is a ‘simple’ and safe procedure. However, there is a known 1–2% major complication rate even in experienced hands,4 and in this survey, 11% of respondents reported a major complication during a VSS procedure, with two reported deaths. Having a life threatening complication from VSS was more commonly reported in higher volume operators, which may naturally be expected due to a higher denominator of cases, or could be secondary to other nuanced factors that this survey was unable to identify.…”
Section: Discussionmentioning
confidence: 60%
“…Meta-analyses of small series of VSS have demonstrated an excellent safety profile with improvement in headaches, pulsatile tinnitus, papilledema, and visual symptoms in the majority of patients 1–3. However, severe complications, including death, have been reported in 1–2% of patients treated with VSS 4. Importantly, very few published recommendations are available5 to guide interested physicians in selecting patients for treatment or for advice on the technical aspects of stenting.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the aforementioned surgeries, venous sinus stenting (VSS) has a relatively favorable complication rate of 6.6%, with a major complication rate (which includes subdural hemorrhage, sinus or stent thrombosis, and retroperitoneal hemorrhage) of 2.3% 14 15. Relapse rates after VSS, however, can vary between 10–26% 16 17.…”
Section: Management Of Vascular Causes Of Ptmentioning
confidence: 99%
“…While headache immediately after stenting due to dural stretch was nearly universal, it was self-limiting within a few weeks. The complication rate here compared favourably with a 2021 multicentre database study (14), which identified 6 major complications from a total of 811 stents and 1,466 catheter venograms for IIH. These authors found 1 fatality after stenting, equating to a mortality of 0.1%.…”
Section: Complications Of Stentingmentioning
confidence: 96%